INTRACRYSTALLINE FRACTIONATION OF OXYGEN ISOTOPES BETWEEN HYDROXYL AND NON-HYDROXYL SITES IN KAOLINITE MEASURED BY THERMAL DEHYDROXYLATION AND PARTIAL FLUORINATION - Girard J.P.; Savin S.M. (My University, 1996)
Thermal dehydroxylation and partial fluorination techniques were used to measure intracrystalline fractionation of oxygen isotopes between hydroxyl and non-hydroxyl sites in kaolinite. Several aliquots of a well characterized, fine-grained (<1 µm) kaolinite from macon, ga, were dehydroxylated in vacuo using a variety of heating procedures, rates, and target temperatures. measured δ18O values of both the liberated water and the dehydroxylated residue are consistent over a wide range of temperatures (550-850°C) when dehydroxylation is performed in a single-step fashion at a rapid heating rate (>50°C/min.). Similar dehydroxylation experiments indicate that brucite dehydroxylation occurs without any significant isotopic fractionation of the oxygen isotopes. By extrapolation we postulate that no significant fractionation occurs during single-step thermal dehydroxylation of fine-grained kaolinite, provided that dehydroxylation is performed under well controlled conditions. In contrast, gibbsite dehydroxylation is accompanied by substantial isotopic fractionation. This is probably the result of the complex, multi-pathway dehydroxylation reaction of this mineral. Similarly, thermal dehydroxylation of coarse-grained (>1 μm) kaolinites and dickites of weathering and hydrothermal origin yield results that are dependent on the temperature of dehydroxylation. We suggest that this effect may be caused by isotopic exchange during diffusion of water molecules through coarse particles.Partial fluorination of fine-grained kaolinite in the presence of excess F2 at low temperatures (<185°C) yields unreproducible δ18O values. When performed at high temperatures (220-240°C) in the presence of insufficient F2, δ18O values are systematically lower than the bulk δ18O value and increase linearly with the percent stoichiometric yield. They are consistent with a greater rate of reaction of hydroxyl oxygen than of non-hydroxyl oxygen, but examination of the isotopic data as well as XRD and IR analyses of the residues after partial fluorination indicates that the separation between the two types of oxygen is not complete. The results, therefore, do not yield a reliable δ18O value of the hydroxyl oxygen.The results of this study suggest that the thermal dehydroxylation technique may be appropriate for analysis of OH groups in fine-grained kaolinite. The partial fluorination approach appears less suitable. Intracrystalline fractionation of oxygen isotopes between hydroxyl and non-hydroxyl sites in kaolinite may be larger than previously reported in experimental studies. Based on the results obtained for the finer-than 1 μm Macon kaolinite a value of 1.0272 is proposed for the intracrystalline fractionation factor, αnon-OH/OH, of kaolinite at 20 +/- 10°C.